Improving Creative Thinking Ability through Innovation of Textbook with Challenge based on STEM Context Learning assisted by Nearpod - Ardiansyah, Adi Satrio; Putri, Rani Rafika; Djouharrochmah, Djouharrochmah (Jurnal Riset Pendidikan Matematika, 2024)
Students must master creative thinking ability in order to face the challenges of learning in the 21st century. However, students' creative thinking abilities at SMP Negeri 1 Ajibarang are still relatively low (43.85). The aim of this research is to develop a textbook that integrated Challenge based on STEM Context Learning assisted by Nearpod that is feasible, easy to understand, effective in improving creative thinking ability, and has a positive response from students. Research and development with the 4D model has been carried out with a sample consisting of two groups, namely class VIII G as the experimental group and class VIII F as the control group. Data was collected through interviews, questionnaires, and tests. Data was analyzed descriptively qualitatively and quantitatively. The results showed that the textbook that integrated Challenge based on STEM Context Learning assisted by Nearpod obtained a feasibility percentage of 93.67% with very feasible criteria, obtained a readability percentage of 95% with easy to understand criteria, effectively improving students creative thinking ability, and obtained very good student responses with percentage of 90.42%. Thus, the textbook that integrated Challenge based on STEM Context Learning assisted by Nearpod can be used as a learning resource that is able to improve students' creative thinking abilities in mathematics learning, especially for material on systems of linear equations in two variables.